"My story is like a goat tied to a hook." Views from a marginalised tribal group in Kerala (India) on the consequences of falling ill: a participatory poverty and health assessment. Issue 6 (23rd October 2009) - Mohindra, K S; Narayana, D; Haddad, Slim
Abstract : Background: Indigenous populations tend to have the poorest health outcomes worldwide and they have limited opportunities to present their own perspectives of their situation and shape priorities in research and policy. This study aims to explain low healthcare utilisation rates and opportunities to cope with illness among a deprived indigenous group - based on their own experiences and views. Methods: A participatory poverty and health assessment (PPHA) was conducted among the Paniyas, a previously enslaved tribal population of South India in a Gram Panchayat in Kerala, India in 2008. Purposive sampling was used to select five Paniya colonies, involving 66 households. Results: There were four key findings. First, Paniyas' perception that the quality of the public healthcare system is poor leads them to seek suboptimal care or deters them from using services. Second, there are significant costs of care unrelated to service use or purchase of medicines, such as travel costs, which the Paniyas lack the ability to pay. Third, illness can lead to loss of productive opportunities among those who fall ill and those who provide informal care. Fourth, the Paniyas lack a 'range' of coping strategies as they are wage labourers without diverse sources of income. They rely on a single strategy: borrowing from outside their community, often from landowners and employers, to whom they become indebted with their labour. Conclusions: Improving the capacity of tribal populations to present their own perspectives is likely to lead to more effective tribal development policies and consequently better health.